The Merchant of Venice on (Polish) Stage: The Past (Tense)? - Jacek Fabiszak; Urszula Kizelbach (Polish Journal of English Studies, 2020)
The aim of the article is to consider a production of The Merchant of Venice in Poland after the publication of Jan Gross’s Sąsiedzi [Neighbours] (2000), which rekindled, or perhaps started, the discussion on the nature of the Polish-Jewish relations. Furthermore, the play itself is considered difficult in the post-Holocaust era. For these reasons, it seems interesting to discuss Szymon Kaczmarek’s production (2019) and the director’s handling of this dramatic and cultural ‘hot potato’. Although Kaczmarek does not refer to Gross’s publication directly, yet he uses the fate of Jewish and female characters in the play to comment on the marginalised in present-day Poland.